Intravenous chemotherapy preparation errors: Patient safety risks identified in a pan-Canadian exploratory study. (February 2014) - White, Rachel; Cassano-Piché, Andrea; Fields, Anthony; Cheng, Roger; Easty, Anthony
Background: This exploratory study was launched following a critical chemotherapy medication incident to thoroughly and proactively examine the current processes for ordering, preparing, labeling, verifying, administering, and documenting ambulatory intravenous chemotherapy in Canada, and to identify factors that may contribute to preventable adverse drug events. Methods: Field observations in six Canadian cancer centers to identify end-to-end processes in clinic, pharmacy, and treatment areas; analysis of processes to identify risks. Results: Three types of previously locally unrecognized potential chemotherapy preparation errors in Canadian oncology pharmacies were uncovered, all of which are undetectable if they occur. Although the frequency of these errors is unknown, their impact is potentially catastrophic. Interpretation: Dispensing errors in high-risk intravenous preparation have been studied in the past, but it is unlikely that these studies have detected these errors because of the inherent limitations of the detection methods used. Research on preparation errors using more sensitive methods is therefore urgently needed to establish the extent to which pharmacy preparation practices may be error-prone, and to allow reliable evaluation of the impact of mitigation strategies. Widespread practice changes in Canadian oncology pharmacies are necessary, and are currently underway.